Faktor yang Mempengaruhi Agresivitas Pajak pada Perusahaan Manufaktur Periode 2015-2020 - Rianto Rianto; Adang Sunandar (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2021)
The purpose of this study is to analyze whether inventory intensity, sales growth, earnings management, and profitability have an effect on tax aggressiveness. In this study, tax aggressiveness is proxied by the Cash Effective Tax Rate (CETR). The data is secondary data obtained from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2020 period. The sampling technique used was purposive sampling. Based on the results of the tests conducted in this study, it was found that the inventory intensity variable had a negative and significant effect on tax aggressiveness. Sales growth variable has a positive and significant effect on tax aggressiveness. Earnings management variable has a positive but not significant effect on tax aggressiveness. Meanwhile, profitability has a positive and significant effect on tax aggressiveness.